2002
DOI: 10.1021/ja020924h
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Electrophilic Attack of a Double Bond Exhibits Stereoselectivity

Abstract: Protonated acetaldehyde (ion 1) reacts with allyltrimethylsilane (allyl-TMS) in the gas phase to yield cis-piperylene (cis-1,3-pentadiene) as the major product. The cis isomer predominates over trans by a factor >/=15:1, a degree of stereoselectivity that is unprecedented in a reaction where the double bond geometry has not been specified in the reactant. The neutral products were assessed by creating tritiated 1 via decay of a tritium nucleus in gaseous ethanol molecules labeled with >1 tritium atom. The radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Both experiments are performed using tandem mass spectrometry. ,,, Because ion/molecule reactions are normally fast and efficient in the gas phase and highly sensitive to the nature of functional groups including fine structural variations such as relative positions of functional groups, product distributions often provide key and diagnostic information for structural characterization of both reactant ions and neutral molecules. For instance, an early and classical application of ion/molecule reactions showed that the simplest amino acid, glycine, adopts an uncharged form in the gas phase, not the zwitterionic form normally found in solution. , Again, a classical group of isomeric gaseous ions, C 7 H 7 + (benzyl, tropylium, and toluyl cations), which are very difficult to distinguish by CID, are easily differentiated through ion/molecule reactions involving electrophilic attack on toluene and dimethyl ether . More interestingly, numerous examples of stereospecific ion/molecule reactions reported in the gas phase are useful for the distinction of stereoisomers, including cases in which NMR encounters severe problems. As an example, consider the gas-phase reaction of Ti + with C 6 H 6 D 6 generated by hydrogenation of C 6 D 6 with a cobalt catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both experiments are performed using tandem mass spectrometry. ,,, Because ion/molecule reactions are normally fast and efficient in the gas phase and highly sensitive to the nature of functional groups including fine structural variations such as relative positions of functional groups, product distributions often provide key and diagnostic information for structural characterization of both reactant ions and neutral molecules. For instance, an early and classical application of ion/molecule reactions showed that the simplest amino acid, glycine, adopts an uncharged form in the gas phase, not the zwitterionic form normally found in solution. , Again, a classical group of isomeric gaseous ions, C 7 H 7 + (benzyl, tropylium, and toluyl cations), which are very difficult to distinguish by CID, are easily differentiated through ion/molecule reactions involving electrophilic attack on toluene and dimethyl ether . More interestingly, numerous examples of stereospecific ion/molecule reactions reported in the gas phase are useful for the distinction of stereoisomers, including cases in which NMR encounters severe problems. As an example, consider the gas-phase reaction of Ti + with C 6 H 6 D 6 generated by hydrogenation of C 6 D 6 with a cobalt catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…104,105 Again, a classical group of isomeric gaseous ions, C 7 H 7 + (benzyl, tropylium, and toluyl cations), which are very difficult to distinguish by CID, are easily differentiated through ion/molecule reactions involving electrophilic attack on toluene 106 and dimethyl ether. 107 More interestingly, numerous examples of stereospecific ion/molecule reactions reported in the gas phase [108][109][110] are useful for the distinction of stereoisomers, including cases in which NMR encounters severe problems. As an example, consider the gas-phase reaction of Ti + with C 6 H 6 D 6 generated by hydrogenation of C 6 D 6 with a cobalt catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…16 One TS for the attack of allyl trimethylsilane to protonated acetaldehyde has been identified. 17 Some TSs have been located for the addition of several γ-substituted allyl trimethylsilanes to a lithiated R,β-unsaturated acid, but without scanning the whole TS space. 18 Keck et al have discussed part of the open TS space (leaving out Z-configurated aldehyde-Lewis acid complexes) for the crotylation of BF 3 -activated aldehydes with crotyl tributylstannane on the basis of steric interaction and possible secondary overlap, but neither experimental nor computational data have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence comes from strained, intramolecular systems, whereas computational investigations have been performed only for simplified systems . One TS for the attack of allyl trimethylsilane to protonated acetaldehyde has been identified . Some TSs have been located for the addition of several γ-substituted allyl trimethylsilanes to a lithiated α,β-unsaturated acid, but without scanning the whole TS space .…”
Section: Introductionmentioning
confidence: 99%
“…The stereoselectivity of vicinal unimolecular eliminations in the gas phase ( syn- eliminations, sometimes called cis -eliminations) has long intrigued organic chemists. , Not long ago we reported a 4-center elimination from a vibrationally activated positive ion, which expels water much more quickly than conformational equilibration can take place. Under those conditions, elimination occurs so promptly that the geometry with which the cation initially forms is preserved, leading to >90% cis stereochemistry of the recovered alkene …”
mentioning
confidence: 99%